Characterization of New HIV Infections among Adults ≥45 Years—New York City, North Carolina, San Francisco, 2011–2013. (4th October 2017) - Evans, Mary; Patala, Anne; Campbell, Ellsworth; Westheimer, Emily; Gay, Cynthia L; Cohen, Stephanie E; Switzer, William M; Peters, Philip J
Abstract: Background: While HIV prevention activities are often focused on younger people, older people can also be at risk for HIV infection. We aimed to characterize HIV transmission in older adults. Methods: The STOP study was a multi-site prospective study of persons with acute HIV infection (AHI) from 2011 to 2013. Older adults were defined as ≥45 years and younger persons were 13–44 years. AHI was defined by a negative rapid test but a reactive antigen/antibody or HIV RNA test. We performed bivariate analysis using Pearson's chi-square and odds ratios to examine associations between older age and transmission characteristics. Among persons with HIV-1 polymerase ( pol) sequences, transmission linkages were inferred when the genetic distance between sequences was <1.5% and did not indicate directionality of transmission. Results: Among 86, 836 participants (median age, 29 years; 75.0% male; 51.8% MSM), HIV infection was diagnosed in 176 (1.46%) of 12, 036 older adults compared with 1, 150 (1.53%) of 74, 800 younger people ( P = 0.56). Among HIV-infected persons, AHI was diagnosed in similar proportions of older and younger people (13.1% vs. 12.6%; P = 0.86). Among HIV-infected persons who participated in partner notification ( n = 1, 326), older adults were less likely to report meeting a sex partner online (11.3% vs. 26.9%; OR 0.52, 95% CI = 0.35–0.78) and were less likely to name ≥2 sex partners (31.5% vs. 46.8%; OR = 0.28, 95% CI = 0.15–0.53) compared with younger people. Among HIV-infected persons with HIV-1 pol sequences ( n = 537), similar proportions of older and younger people had viruses that genetically linked with another study participant (15.9% vs. 23.5%; OR 0.62, 95% CI 0.31–1.22) (Figure). Conclusion: In this study, older adults had a similar frequency of newly diagnosed HIV infection, acute infection, and genetic linkage compared with younger people, suggesting that increased HIV prevention efforts may be needed in this population. Disclosures: All authors: No reported disclosures.